Model Solusi Inovatif Pembiayaan Spesifik Perbankan Pada Agribisnis Komoditi Padi di Sulawesi Selatan - Sjamsir, Zulkfili; Hamzah, H; R, Suhartina (Journal Galung Tropika, 2023)
Traces of the long history of agricultural credit history in Indonesia are divided into (i) Pre-Bimas (1964); (ii) National Community Guidance and Gotong Royong (1965-1970); (iii) Improved Guidance (1970-1984); (iv) Agricultural Business Credit (1985-1999); (v) Food Security Credit (2000), Food and Energy Security Credit (2007) and People's Business Credit (2007 to present). However, until now there has not been a single consistent credit scheme that specifically deals with rice commodities. Thus, the capacity building of rice farmers in adopting advanced technologies such as quality seeds, balanced fertilizers, water pumping machines, tractors, power threshers, combine crushers, and processing of products based on the industrial revolution 4.0 in order to increase the added value of rice food agricultural products cannot be realized. Research objectives include; 1. Assess the constraints/obstacles in the distribution of rice commodity agribusiness business financing schemes from the perspective of financial institutions and rice commodity agribusiness farmers and 2. Design innovative banking-specific financing solutions models for rice commodity agribusiness businesses. This research was conducted from August to December 2022, in Gowa Regency, South Sulawesi Province. The results of this collaborative research can be stated: (1) Obstacles/obstacles in terms of bank lending are relatively centralized lending policies and from the agribusiness farmer's side are weak financial administration systems and lack of bankable guarantees; and (2) The model for innovative banking-specific financing solutions for rice commodity agribusiness produced in the research is the Rice Agribusiness Credit Skim (KAP), in which the role of the Regional Government is as Advisor and Coordinator.